CSR information, environmental awareness and CSR diffusion in SMEs of Angola - Paiva, I. C. de S. (2023)
Purpose – With the increasing awareness of sustainability and its importance around the world, corporate social responsibility (CSR) in Africa also requires attention. Based on the stakeholder theory, this study aims to determine the relationship between CSR information received by small and medium-sized enterprises (SMEs) and CSR’s diffusion and the mediating role of environmental awareness in Angola as a country representative of the African context. Design/methodology/approach – The empirical study analyzes managers’ perceptions of 131 SMEs in Angola. The partial least squares structural equation modeling (PLS-SEM) is the method to assess the relationship between CSR information and its diffusion and the mediating role of environmental awareness SMEs in Angola. Findings – The authors found strong evidence that CSR diffusion, and disclosure as one of CSR’s related actions, heavily depends on the information received and managed by the firm. The authors also confirmed that environmental awareness puts pressure on SMEs to increase the SMEs’ diffusion efforts. Practical implications – The study points out the role of managers in promoting a responsible orientation of businesses in Angola for preserving the environment and improving the competitive success of SMEs. Social implications – The social, economic and legal contexts of Angola are vulnerable. The findings raise concerns about whether governments and regulatory efforts improve the development of the strategies toward social responsibility of African firms and whether these firms also increase the role of SMEs in producing positive outcomes through CSR. Originality/value – The results of this study contribute to a better understanding of the features of the strategic orientation of SMEs in Angola, necessary to enhance CSR and protect the environment. The conclusions highlight the potential role of managers in promoting a culture of ethics, social innovation and successful competition change in businesses.